PENCEGAHAN PORNOGRAFI DAN PORNOAKSI DIHUBUNGKAN DENGAN KASUS “BUGIL” DI BANDARA YOGYAKARTA DALAM PRESPEKTIF HUKUM ISLAM - Nurhasanah, Neneng; Nurel Alam, Fahry Zen; Prayoga, Adrian Mohammad (Jurnal Dialektika Hukum, 2023)
Technological developments are a cause of a person experiencing changes from social interaction, social order habits in dealing with each other, pornography and pornography nowadays are widely circulated or there are many people with the intention of stimulating one's lust through social media, examples of cases that are currently hot are related to a viral video on Twitter of a naked woman in the Yogyakarta International Airport (YIA) area in Kulon Progo, Yogyakarta Special Region. In the video, the woman with sunglasses and face covered with a mask filmed herself taking off her gray suit and dark skirt until she was half naked, the video with a duration of 1 minute 23 seconds showed the woman then doing something indecent alone. The author uses a normative juridical method, namely reviewing secondary data used in this study is a literature study. The data analysis method of this research is qualitative. The results of research on cases of pornography and porno-action have not met a common ground for solving the problem as if it became a natural thing.